Analysis of the Effect of Diluent for Rehydration of PoulVac® MycoF on Vaccination Seroconversion Results - Leigh, S.A.; Branton, S.L.; Collier, S.D.; Evans, J.D. (International Journal of Poultry Science, 2011)
Direct eye drop vaccination of poultry using live Mycoplasma gallisepticum vaccines provides the most efficient route of vaccination. The research reported in this study examines the effect of diluent used to rehydrate lyophilized M. gallisepticum vaccines on its ability to induce a measurable humoral immune response in the host. The results suggest that during the initial time period following vaccination, significant differences between the treatment groups are found. However, these differences between the diluents are unlikely to significantly impact the final outcome of vaccination when considered over the life of the host.